2011
DOI: 10.1128/jcm.05323-11
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Direct Plating, Broth Enrichment, and Specimen Source on Recovery and Diversity of Methicillin-Resistant Staphylococcus aureus Isolates among HIV-Infected Outpatients

Abstract: We compared recovery of Staphylococcus aureus and methicillin-resistant S. aureus (MRSA) from nasal and groin swab specimens of 600 HIV-infected outpatients by selective and nonselective direct plating and broth enrichment. Swabs were collected at baseline, 6-month, and 12-month visits and cultured by direct plating to mannitol salt agar (MSA) and CHROMagar MRSA (CM) and overnight broth enrichment with subculture to MSA (broth). MRSA isolates were characterized by pulsed-field gel electrophoresis (PFGE), staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
1
14
1
Order By: Relevance
“…It should be noted that the study size limits the detection of small differences in sensitivity. The most striking finding of this study is that almost half of all MRSA isolates remained undetected when using direct culture only, an observation which confirms previous reports that broth enrichment is essential for detection of MRSA (1,(3)(4)(5).…”
supporting
confidence: 78%
“…It should be noted that the study size limits the detection of small differences in sensitivity. The most striking finding of this study is that almost half of all MRSA isolates remained undetected when using direct culture only, an observation which confirms previous reports that broth enrichment is essential for detection of MRSA (1,(3)(4)(5).…”
supporting
confidence: 78%
“…Swabs were incubated at 37°C for 24 hours in tryptic soy broth (Remel Inc.) and streaked a second time onto MSA. 18 Colonies from all MSA cultures resembling S. aureus were subsequently inoculated into tryptic soy agar (TSA) and transported to the University of Texas School of Public Health in Houston for additional testing. In Houston, cultures were regrown on MSA and then incubated at 37°C for 24 hours on blood agar, to assess hemolysis and test for coagulase activity (BactiStaph Latex 450; Remel Inc.), and on TSA, to test for catalase activity (Sigma, St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…One possible explanation for this observation is that CA-MRSA strains might preferentially colonize at nonnasal body sites. The throat and groin have been implicated as important sites of S. aureus and MRSA colonization among certain patient populations (8,9), and other studies have suggested that colonization patterns of CA-MRSA strains may be distinct from those of health care-associated MRSA strains (10,11). The epidemiology of community-associated S. aureus colonization and its role in subsequent infection are not well characterized in the United States.…”
mentioning
confidence: 99%